PETROLOGY OF THE VOLCANIC FILL IN THE LASHKEREK CALDERA (UZBEKISTAN) AND THE PROBLEM OF HETEROGENIZATION OF ACID LAVAS - Rusinov V.L. (My University, 2001)
The Lashkerek caldera filled with acid volcanic products is situated in the Kurama Ridge near Tashkent (Uzbekistan). These eruptions of the Late Paleozoic time were predominantly of the explosive type. The erupted complex of quartz porphyry tuff, ignimbrite, and rhythmically banded fluidal lavas of trachyrhyolite composition encloses explosive breccias and dikes of granodiorite-granite porphyries and felsites. Many of these magmatic rocks reveal features characterizing different mechanisms of liquid immiscibility. The diverse results of magma heterogenization depended on dynamics and conditions of magma cooling. Magma fractions that originated by the quasi-equilibrium liquid immiscibility considerably differ from each other in their silica content. By the fast and strong overcooling, the heterogenization developed in accordance with the metastable spinodal mechanism, and produced melt phases are similar in composition to each other. In felsitic dikes, the layering appeared in moving magma when flow rates were differentiated. The spinodal mechanism of nonequilibrium magma heterogenization was in action either by a weak convection in the magma chamber, or during thermal oscillations that affected the diffusion rate. The necessary condition for the last mechanism is an intense escape of volatile components from the melt. In ignimbrites, quartz phenocrysts are typical of fiamme rich in silica, whereas similar vitric lenses depleted in silica contain plagioclase phenocrysts owing to position of binodal or spinodal segments on both sides of the quartz-feldspar eutectic. In this case, the liquid immiscibility took place in magmatic chamber parallel to crystallization of intratelluric phenocrysts at the temperature of about 900 degreesC and under pressure up to 5 kbar. The excess pressure was conditioned by the fluid influx from the depth into the magma chamber.
Keywords: Lashkerek caldera; Uzbekistan; Paleozoic; Nonequilibrium magma heterogenization; Paleozoic; Палеозой